Gerenciamento de resultados mediante decisões operacionais e sustentabilidade corporativa no Brasil - Cunha, Estephanye Paganotti da (2016)
The objective of this dissertation is to analyze the relationship between earnings management through operational decisions and factors of corporate sustainability of non-financial companies listed on BM&FBOVESPA. The detection of earnings management for operational decisions is by means of the waste (errors) of the regression and represent an abnormal level of real activities of the company, so they are a proxy for this form of management (Paulo, 2007). In a review of the literature on this theme, it was found that there is a gap in research on earnings management in the context of Corporate Sustainability, given that there are few studies that address the theme and the results are divergent. Thus, in this study, we used a sample totaling 1445 observations in the period from 2005 to 2015, collected by system Comdinheiro. For the operationalization of the research, made use of the regression analysis by the model Pooled Ordinary Least Squares (POLS) panel, with standard errors robust cluster by sector and year. The results obtained, suggest there is no relationship between the practice of earnings management through operational decisions and the entry of companies in the ISE portfolio analysis, however, between the variables related to factors of corporate sustainability, it was verified positive relationship in the three models of operational manipulations used between the disclosure of corporate sustainability based on the GRI and results management through operational decisions. It is concluded that the entry of companies in the ISE portfolio does the influences in manipulate their operating results, and this finding corroborates the study by Silva (2014). However, the data indicate that the companies use corporate sustainability in order to practice earnings management through operational decisions, as well as identifies himself in the research of Prior, Port and Tribó (2008); Salewski and Zülch (2014); Heltzer (2011) and Beuren and Rodrigues Junior (2014)